2005
DOI: 10.3354/meps292159
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of Sargassum ilicifolium (Phaeophyta) on a shallow reef flat in the southern Red Sea (Eritrea)

Abstract: The seasonality of Sargassum ilicifolium was studied in the southern Red Sea by monitoring thallus density, thallus size and the initiation, growth, reproduction and survivorship of primary laterals. Thallus density showed slight but significant seasonal variation; it was highest at the end of the hot season and lowest at the end of the cold season. Mean thallus and lateral lengths peaked in the second half of the cold season. Initiation of new laterals was highest in the first half of the cold season. High la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 48 publications
5
67
1
1
Order By: Relevance
“…Asynchronous cycles and a complex interchange of different genera within the macroalgal understory also occurred in locationspecific patterns in response to changing Sargassum canopy biomass. While our findings support the hypothesis that temperature is a primary driver of seaweed seasonality in many tropical reef systems (Glenn et al 1990;Martin-Smith 1993;Ateweberhan et al 2005), Ningaloo yields a unique perspective on the drivers and consequences of Sargassum seasonality within a coral reef ecosystem experiencing wide ranges in sea temperature.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Asynchronous cycles and a complex interchange of different genera within the macroalgal understory also occurred in locationspecific patterns in response to changing Sargassum canopy biomass. While our findings support the hypothesis that temperature is a primary driver of seaweed seasonality in many tropical reef systems (Glenn et al 1990;Martin-Smith 1993;Ateweberhan et al 2005), Ningaloo yields a unique perspective on the drivers and consequences of Sargassum seasonality within a coral reef ecosystem experiencing wide ranges in sea temperature.…”
Section: Discussionsupporting
confidence: 78%
“…We found that sea temperature conditions 1-month prior to the standing biomass, in concert with the spatial factor of location, provided the single best explanation for Sargassum biomass variation throughout two full growth-decay cycles at Ningaloo. Such prevalence of a single forcing factor could be a reflection of the high variation in sea temperature at Ningaloo, where the 7uC range in mean monthly sea temperatures (at both locations) exceeds that recorded for Sargassum beds in the Caribbean (3.9uC; Ferrari et al 2012), Hawaii (5uC;Glenn et al 1990), the southern Red Sea (5.7uC; Ateweberhan et al 2005), and the central Great Barrier Reef (6.7uC; Lefevre and Bellwood 2010). Such temperature effects were strongly dependent on spatial context in our study, with roughly half of the Sargassum biomass variation attributable to spatial factors.…”
Section: Discussionmentioning
confidence: 91%
“…survival and growth) in Sargassum and many other fucoid algae has been reported by various authors (McCourt, 1985;Ang, 1992;Å berg, 1996;Gillespie & Critchley, 2001). However, no direct trade-off was found between reproduction and growth in populations of Sargassum ilicifolium, Turbinaria triquetra, and S. subrepandum, as reported by Ateweberhan et al (2005Ateweberhan et al ( , 2006Ateweberhan et al ( , 2008. All previous studies involving energy tradeoffs were descriptive rather than designed experiments, perhaps because resource allocation cannot be directly quantified.…”
Section: Introductionmentioning
confidence: 89%
“…The distribution and population structure of Sargassum species were influenced by water temperature, tidal levels, water movement and substrate types (i.e., rocky shores) (Ang, 1986;Ateweberhan et al, 2005). Indonesia is a tropical country that has two seasons, rainy and dry season.…”
Section: Introductionmentioning
confidence: 99%